Libraries in 17th century Nueva Granada: The library of Fray Cristóbal de Torres at Colegio Mayor de Nuestra Señora del Rosario - García, María del Rosario (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article comprises a visit to the library of Fray Cristóbal de Torres, an exemplary reader in 17th century Nueva Granada, Archbishop of Santafé de Bogotá and founder of Colegio Mayor de Nuestra Señora del Rosario. The nature of this library is analyzed in comparison to others from the time, as well as some aspects related to the circulation of knowledge in Spain and America, through the analysis of the texts donated to Colegio Mayor del Rosario by the archbishop. Likewise, this article presents some conclusions regarding the conditions of education in 17th century Nueva Granada.